Implementasi Manajemen Strategik pada Lembaga Pendidikan Majelis Taklim Darunnajah Desa Bejiruyung Kecamatan Sempor Kabupaten Kebumen - Akh. Kheroni (LPPM IAINU Kebumen, 2020)
This study discusses the implementation of strategic management at the Darunnajah Taklim Assembly at Bejiruyung Village, Sempor District, Kebumen Regency. it is intended to answer the following problems: (1) What about the Darunnajah Taklim Assembly Educational Institution in Bejiruyung Village, Sempor District, Kebumen Regency? (2) How is the implementation of the strategy at the Darunnajah Taklim Assembly Educational Institution in Bejiruyung Village, Sempor District, Kebumen Regency? (3) What is the strategic evaluation of the Darunnajah Taklim Assembly Educational Institution in Bejiruyung Village, Sempor District, Kebumen Regency? These problems are discussed through field studies. This type of research is qualitative research. The data was obtained by means of observation, interviews and documentation. All data obtained is then analyzed by data reduction, data display and verification or drawing conclusions. The results of the study found that: (1) The strategic planning of the Darunnajah Kebumen Taklim Assembly includes several activities carried out, namely developing vision, mission and objectives, identifying internal and external factors through SWOT analysis techniques, short, medium and long term planning, and determining strategies excellence in improving the quality of education. The strategic planning of the Darunnajah Taklim Council at Bejiruyung Sempor Village is carried out collectively by the chairman, administrators, religious and community leaders and village officials; (2) The implementation of the strategic management of the Darunnajah Taklim Assembly includes the activities carried out, namely determining organizational policies, motivating administrators and congregations, allocating human resources, and developing organizational culture. The results of the implementation of strategic management produced at the Darunnajah Taklim Assembly in Bejiruyung Sempor Village, namely increased human resource performance, an effective program implementation process, and high community attractiveness; (3) Evaluation of the management of the Darunnajah Taklim Assembly in Bejiruyung Village, Sempor District, Kebumen Regency, namely monitoring all the results of activities from the planning and implementation of strategic management, and taking corrective steps.